2017
DOI: 10.1177/0885328217734824
|View full text |Cite
|
Sign up to set email alerts
|

Cryogel scaffolds from patient-specific 3D-printed molds for personalized tissue-engineered bone regeneration in pediatric cleft-craniofacial defects

Abstract: Bone defects are extremely common in children with cleft-craniofacial conditions, especially those with alveolar cleft defects and cranial defects. This study used patient-specific 3D-printed molds derived from computed tomography and cryogel scaffold fabrication as a proof of concept for the creation of site-specific implants for bone reconstruction. Cryogel scaffolds are unique tissue-engineered constructs formed at sub-zero temperatures. When thawed, the resulting structure is macroporous, sponge-like, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…Therefore, to reinforce the strength of the cryogel for compression or other types of stress and to increase biocompatibility and accelerate biomineralization of the cryogel, HA was introduced. Mechanical measurements showed that addition of HA significantly increased the elastic modulus of CHI-PVA-HA-Hep-GA cryogel (1085 ± 428 kPa) and that the value was significantly higher in comparison to other cryogel-based scaffolds designed for bone regeneration [43][44][45][46][47][48][49]. Degradation experiments confirmed a decreased in vitro degradation rate of HA-containing cryogels, which is in line with other published data [45,50].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, to reinforce the strength of the cryogel for compression or other types of stress and to increase biocompatibility and accelerate biomineralization of the cryogel, HA was introduced. Mechanical measurements showed that addition of HA significantly increased the elastic modulus of CHI-PVA-HA-Hep-GA cryogel (1085 ± 428 kPa) and that the value was significantly higher in comparison to other cryogel-based scaffolds designed for bone regeneration [43][44][45][46][47][48][49]. Degradation experiments confirmed a decreased in vitro degradation rate of HA-containing cryogels, which is in line with other published data [45,50].…”
Section: Discussionsupporting
confidence: 89%
“…While early attempts at prosthesis printing were problematic, mainly due to the materials involved, 10 this area nevertheless holds great promise for the future, as printing methods improve and material selections expand. 3D printing has also been used to create CT-derived molds for tissue materials that cannot be printed, because of their nanoscale structure, 13 and to create hollow vascular structures which can be incorporated into flow phantoms. 12,14 Recently, there have been attempts to use various 3D printing technologies for constructing radiopaque objects.…”
Section: Introductionmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate craniofacial tissue engineering 49‐72,74‐77,79,81‐84,145‐197 …”
Section: Discussionmentioning
confidence: 99%